2020
DOI: 10.1051/matecconf/202032301016
|View full text |Cite
|
Sign up to set email alerts
|

Modification of early strength parameters of concrete by the addition of fly ash and admixture of nano C-S-H for application in 3D printing

Abstract: In the paper, the authors present the results of tests concerning traditional cement mortars with the addition of silica fly ash and the C-S-H nano-admixture. The use of fly ash results in improved plasticity of the mixture. The use of the C-S-H nano-admixture has a positive effect on shortening the setting time and a rapid increase in the strength of mixtures without losing their subsequent properties, which is presented in the research described in the paper. On this basis, the impact of fly ash and the nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Earlier studies [49] demonstrated that a high compressive strength, along with rheological properties, were found to be influential in attaining a good dimensional accuracy in concrete 3D printing. Accordingly, early strength development, similar to those observed in RMS-OP and RMS-HMP mixes presented in this study, was also found to be critical in concrete 3D printing applications [50,51]. When these factors were taken into account, the two best-performing mixes, RMS-OP and RMS-HMP, were chosen for further analysis leading up to their future potential use in 3D printing applications.…”
Section: Compressive Strengthsupporting
confidence: 62%
“…Earlier studies [49] demonstrated that a high compressive strength, along with rheological properties, were found to be influential in attaining a good dimensional accuracy in concrete 3D printing. Accordingly, early strength development, similar to those observed in RMS-OP and RMS-HMP mixes presented in this study, was also found to be critical in concrete 3D printing applications [50,51]. When these factors were taken into account, the two best-performing mixes, RMS-OP and RMS-HMP, were chosen for further analysis leading up to their future potential use in 3D printing applications.…”
Section: Compressive Strengthsupporting
confidence: 62%
“…An increased amount of heat released during maturation may adversely affect the value of the rheological contraction. However, the studies presented in [62] confirm the lack of such an effect when using the NA. During the whole maturation period (from 1 to 90 days), in samples modified with FA and admixture, a lower shrinkage value was observed compared to samples without NA.…”
Section: Hydration Heat Test Resultsmentioning
confidence: 70%
“…Cheng et al [ 44 ] reported an improvement in the thixotropic behavior of 3D-printable concrete with the addition of bentonite. Szostak and Golewski [ 169 ] added nano-calcium silicate hydrate (CSH) seeds in concrete and observed a reduction in setting time and a rapid increase in earlier strength. Nano-graphite platelets increase the thermal conductivity of cementitious materials and induce self-sensing capability in concrete.…”
Section: Printable MIX Designs and Influence Of Concrete Ingredients On Rheologymentioning
confidence: 99%